Eudaimonic Well-Being of Management Education Teachers: Role of Big Five Personality Traits using Structural Equation Modeling - Soni, Pooja; Bakhru, Kanupriya Misra (Prabandhan: Indian Journal of Management, 2019)
Stress has risen immensely among teachers in management education as institutes transform into knowledge hubs with a main focus on technological advancement in teaching pedagogy and improvement in quality of research and innovation behavior. This stress among teachers promotes focus on their well-being. Most studies have focused on improving teachers' subjective well-being. However, limited work has been done in understanding the eudaimonic well-being (EWB) of teachers in transforming higher education as well as the role of teacher personality in escalating EWB. The purpose of this study was to examine the relationship between the big five personality traits and EWB of teachers in management education. Data were collected from 504 business school teachers through a structured questionnaire from the national capital region (NCR) of India. Analysis was done using structured equation modeling. The results of the study indicated a positive significant impact of the big five personality traits on eudaimonic behavior of teachers which added to their well-being. The framework provided in the study can aid in producing interventions to improve EWB of teachers in management education, which will ultimately contribute to better quality of education, student well-being, and prosperity of teacher's health. The findings can also help in occupational job design and organizational outcomes in the higher-education sector. This study added knowledge to the domain of big five personality traits, EWB, and their interrelationship from the perspective of management education teachers.